2009
DOI: 10.1016/j.neuron.2009.07.012
|View full text |Cite|
|
Sign up to set email alerts
|

Category-Specific Organization in the Human Brain Does Not Require Visual Experience

Abstract: Summary The ventral stream refers to a neural pathway that projects from early visual areas through to anterior temporal cortex, and comprises regions in ventral and lateral occipital-temporal cortex. The ventral stream is critical for recognizing visually presented objects. Functional imaging studies of the human brain have shown that different regions within the ventral stream show differential activation to nonliving (tools, houses) and living stimuli (animals, faces). The causes of these category preferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
215
3
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 318 publications
(245 citation statements)
references
References 45 publications
26
215
3
1
Order By: Relevance
“…The idea that dimensions of organization that have nothing to do with category per se interact with statistical regularities in experience has recently gained momentum (e.g., Baker et al, 2007; Srihasam et al, 2014). One difficulty faced by proposals that assume a critical role for visual experience in driving category-specificity is that the broad organization by semantic domain in the ventral stream is present even in individuals with no visual experience (Striem-Amit et al, 2012; Mahon et al, 2009; Buchel et al, 1998; He et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The idea that dimensions of organization that have nothing to do with category per se interact with statistical regularities in experience has recently gained momentum (e.g., Baker et al, 2007; Srihasam et al, 2014). One difficulty faced by proposals that assume a critical role for visual experience in driving category-specificity is that the broad organization by semantic domain in the ventral stream is present even in individuals with no visual experience (Striem-Amit et al, 2012; Mahon et al, 2009; Buchel et al, 1998; He et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Tools and other manipulable objects are an ‘eccentric’ class of things in the world for which both surface texture information (relevant for grasping) and action information (relevant for functional use) must be brought into register with visual form. For that reason, the underlying neural code in that region relates tool-specificity to connectivity to parietal action systems (Mahon et al, 2007; for evidence and discussion, see Almeida et al, 2013; Chen and Rogers, 2014; Gallivan et al, 2013; Hutchison et al, 2014; Mahon et al, 2009; 2013; Osher et al, 2015; Stevens et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of studies have provided evidence for functional constancy in blind individuals. These showed that the visual-motion area of the brain responds to auditory and tactile motion 4, 5, 6 , that sounds made by objects are represented in brain regions associated with visual-object recognition 7, 8 , and that reading Braille elicits brain responses in the visual word-form area 9 .…”
mentioning
confidence: 99%